The Relationship between Circulation and Space in Architecture: An Investigation on the Integration of Supermarkets in Shopping Centers - Mohammed Reza Adibi (Architecture Image Studies Scientific Journal)
It is aimed to rank the installation forms in terms of the entrance area in terms of which actions should be at the forefront in the organization of the space, and to examine them in order of importance, to analyze and report on the selected shopping centers comparatively. Known as a temporal and perceptual concept that connects the sequences of spaces or different indoor and outdoor environments, circulation is one of the broad and very important issues in architecture and has become a design discipline that must be done within the framework of certain standards. In looking at the circulation structure framework, the way it is perceived, its main components, forms, horizontal and vertical planes and phases during use all play an important role in architecture.In this research, the relationship and interaction with the user, functionality requirements and accessibility levels of selected shopping malls in terms of circulation integration, for example; the relationship of the orientation areas from the main entrance of the shopping mall to the supermarket entrances with circulation or the parking area and the circulation line of the users will be. In this research, it is aimed to review the literature, examine selected venues (Kanyon Mall, Zorlu Center Mall) in the context of the principles of the circulation layouts, observe the clarity and perceptibility levels of the venue, document it by taking photographs from the selected places, and examine the examples.